The effect of whole-body vibration therapy on bone metabolism, motor function, and anthropometric parameters in women with postmenopausal osteoporosis. Issue 22 (23rd October 2017) - Luo, Xiaotian; Zhang, Jifeng; Zhang, Chi; He, Chengqi; Wang, Pu
Abstract: Purpose: To review the research literature on the effectiveness of whole-body vibration (WBV) therapy in women with postmenopausal osteoporosis. Methods: A systematic review was conducted by two independent reviewers. Mean differences (MDs), standardized mean differences (SMDs), and 95% confidence intervals (CIs) were calculated, and heterogeneity was assessed with the I 2 test. The Cochrane risk of bias tool was used to assess the methodological quality of the selected studies. Results: Nine randomized controlled trials involving 625 patients met the inclusion criteria. No significant improvement was found in bone mineral density (BMD) (SMD = −0.06, 95%CI= −0.22–0.11, p = 0.50); bone turnover markers (MD = −0.25, 95%CI= −0.54–0.03, p = 0.08); anthropometric parameters, including muscle mass, fat mass, body mass index (BMI), and weight (SMD = 0.02, 95%CI= −0.16–0.21, p = 0.81); or maximal isotonic knee extensor strength (SMD = 0.16, 95%CI= −0.63–0.95, p = 0.69). However, maximal isometric knee extensor strength improved (SMD = 0.71, 95%CI = 0.34–1.08, p = 0.0002). Conclusions: WBV is beneficial for enhancing maximal isometric knee extensor strength, but it has no overall treatment effect on BMD, bone turnover markers, anthropometric parameters, or maximal isotonic knee extensor strength in women with postmenopausal osteoporosis. Implication of rehabilitation: Osteoporosis is the leading underlying cause of fractures in postmenopausal women, whole body vibration (WBV) has received much attention as a potential intervention for the management of osteoporosis in recent years. Whole body vibration is beneficial for enhancing maximal isometric knee extensor strength in women with postmenopausal osteoporosis. Whole body vibration has no overall treatment effect on bone mineral density, bone turnover markers, anthropometric parameters and maximal isotonic knee extensor strength in women with postmenopausal osteoporosis.